2019
DOI: 10.3390/met9121279
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Linear and Nonlinear Ultrasonic Parameters in Characterizing Grain Size and Mechanical Properties of 304L Stainless Steel

Abstract: Ultrasonic nondestructive techniques can be used to characterize grain size and to evaluate mechanical properties of metals more practically than conventional destructive optical metallography and tensile tests. Typical ultrasonic parameters that can be correlated with material properties include ultrasonic velocity, ultrasonic attenuation coefficient, and nonlinear ultrasonic parameters. In this work, the abilities of these ultrasonic parameters to characterize the grain size and the mechanical properties of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…Furthermore, these random textures owing to the fast cooling rate have been reported to contain a high dislocation density, which can also contribute to the increased [ 33 ]. In addition, a previous study [ 37 ] reported that a decrease in the grain size increases the number of grain boundaries in a unit volume, in which the grain boundaries often act as interfacial discontinuities and generate higher harmonics for the propagating ultrasonic wave. To further substantiate this observation, the high-angle grain-boundary maps for the 0.92 m/s (grain size: 75 μm) and 1.16 m/s (grain size: 59 μm) LBS conditions were obtained using EBSD and compared, as shown in Figure 10 , where grain boundaries with a misorientation angle exceeding 15° are illustrated by gray lines [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these random textures owing to the fast cooling rate have been reported to contain a high dislocation density, which can also contribute to the increased [ 33 ]. In addition, a previous study [ 37 ] reported that a decrease in the grain size increases the number of grain boundaries in a unit volume, in which the grain boundaries often act as interfacial discontinuities and generate higher harmonics for the propagating ultrasonic wave. To further substantiate this observation, the high-angle grain-boundary maps for the 0.92 m/s (grain size: 75 μm) and 1.16 m/s (grain size: 59 μm) LBS conditions were obtained using EBSD and compared, as shown in Figure 10 , where grain boundaries with a misorientation angle exceeding 15° are illustrated by gray lines [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The parameter , which is another linear ultrasonic property, quantifies the ultrasonic amplitude loss due to scattering, absorption, or friction when ultrasonic waves propagate through a material [ 16 ]. is often dependent on microstructural features such as grain size, boundary [ 37 ], textures [ 38 ], pores [ 12 ], and inclusions [ 39 ]. For conventional metals, nondestructive evaluation of various microstructural features using ultrasonic forward or backscattering has been extensively reported [ 40 ].…”
Section: Description Of Ultrasonic Velocity Attenuation and Nonlinear...mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples used in this study are hot rolled steel plates S355, S275, Corten B and S275N with chemical composition shown in Table 1 that have been based on the European standards and recent research work [10][11][12][13][14][15][16]. Figure 1 depicts the dimension of the prepared samples which correspond to 160mm x 60mm x 30mm for the analysis and characterizations of their microstructure with ultrasonic testing NDT.…”
Section: Methodsmentioning
confidence: 99%
“…Nonlinear ultrasonic detection methods can be divided into the high-order harmonics detection method [24,25], the mixing modulation method [26][27][28], and the ultrasonic phased array imaging detection method [29], of which the high-order harmonics detection method is the most mature and widely used. Addressing the problem that SLM 316L stainless steel parts are prone to fatigue damage in multiple working conditions, and based on the nonlinear acoustics theory, in this study, the nonlinear ultrasonic test for the SLM 316L stainless steel specimen, which was subjected to fatigue loading, was carried out using the high-order harmonics detection method.…”
Section: Introductionmentioning
confidence: 99%